Electrochemical characterization of highly abundant, low cost iron (III) oxide as anode material for sodium-ion rechargeable batteries. (10th April 2018) - Fiore, Michele; Longoni, Gianluca; Santangelo, Saveria; Pantò, Fabiola; Stelitano, Sara; Frontera, Patrizia; Antonucci, Pierluigi; Ruffo, Riccardo
Abstract: The development of sodium ion batteries as alternative technology to the lithium ion depends on the design of electrode based on cheap and high abundant elements. Iron oxides are potentially good candidates as negative electrode thanks to their high specific capacity, but they suffer from poor electronic transport properties and large volume change during sodiation/de-sodiation cycles. Stable performance in hematite or magnetite based electrodes requires the use of Fe/C composites made by expensive carbon precursors such as graphene oxides or carbon nanotubes. However, the limits of iron (III) oxide can also be tackled using a different approach by combining the advantages of the nanostructuring and the doping with an aliovalent element. In this work, we present for the first time the use of Si-doped Fe2 O3 nanofibres obtained by an easy scalable process based on the electrospinning method. The silicon doping does not just improve the transport properties but induces also changes in the structure and morphology. The electrochemical results show that the Si-doped Fe2 O3 fibres deliver an anodic capacity of 350 mAh·g −1 at the average potential of 1.5 V vs. Na + /Na after 70 cycles, a result never achieved for iron oxide based electrode standard formulation.